The Effect of Reporting Technique on Students’ Speaking Skill - Nofi Sri Rejeki; Agus Mulyana; Tenia Rahmalia (Foremost Journal, 2021)
ABSTRACT Speaking is a tool of communication. Speaking is important to learn, especially in learning English language. However, there are still many students cannot speak English fluently. This research used quasi-experimental design which was intended to find out whether there is any effect of students' speaking skill after using reporting technique by reporting an analytical text at the eleventh grade of SMA Negeri 20 Kabupaten Tangerang. The instrument was tested when students practiced monologue on recorder and video. The normality test used non-parametric test one-sample Kolmogorov-Smirnov test. The result of the normality test was not normal distributed. The homogeneity result of this research was concluded that the variants both data pre-test and post-test in the students' speaking skill are homogenous. Meanwhile, for the test of  difference on this research uses Wilcoxon Signed Ranks Test. Therefore, H0 is rejected and Ha accepted. It can be concluded that there is an average different between the pre-test and post-test learning outcomes. It means that there is significant effect of reporting technique on students' speaking skill at the eleventh grade in SMA Negeri 20 Kabupaten Tangerang in academic year 2020/2021.